Cross-cultural adaptation and validation of the ABIS questionnaire for French speaking amputees: French validation of the ABIS questionnaire. Issue 5 (27th February 2020) - Vouilloz, Aurélie; Favre, Christine; Luthi, François; Loiret, Isabelle; Paysant, Jean; Martinet, Noël; Lacraz, Alain; Suva, Domizio; Lambert, Jean; Borens, Olivier; Vuistiner, Philippe
Abstract: Background : The Amputee Body Image Scale (ABIS) and its shortened version (ABIS-R) are self-administered questionnaires to measure body image perception of amputee. Our aim was to assess the validity and reliability of the French ABIS (ABIS-F and ABIS-R-F). Methods: Ninety-nine patients were included. The cross-cultural adaptation was performed according to the recommendations. Construct validity was assessed by measuring the correlation between ABIS-F or ABIS-R-F scores and quality of life, pain, anxiety, and depression. Internal consistency was measured with Cronbach's α. The standard error of measurement, smallest detectable change, Bland and Altman limits of agreement, and intraclass correlation were the measures of agreement and reliability. Results: A highest body image disturbance was associated with lowest quality of life, higher pain, and higher anxiety, and depression. Cronbach's α was 0.91/0.89 (ABIS-F/ABIS-R-F). The standard error of measurement was 5.35/2.28 (ABIS-F/ABIS-R-F). The smallest detectable change was 14.82/6.31 (ABIS-F/ABIS-R-F). The mean difference in ABIS-F score was −3.90 with limits of agreement from −18.71 to 10.92. For ABIS-R-F, the mean difference was −2.12 with limits of agreement from −8.43 to 4.19. Intraclass correlation was 0.87/0.82 (ABIS-F/ABIS-R-F). Conclusions : The French versions ABIS-F and ABIS-R-F share similar psychometric properties, both are as reliable, but ABIS-R-F has a better response structure and is more feasible. Implications for rehabilitation: The quality of life of amputees is impacted by their satisfaction with body image The Amputee Body Image Scale questionnaire measures this perception and is available for French-speaking amputees The Standard Errors of Measurement proposed could be useful for clinical and research purposes Both ABIS and ABIS-R showed satisfactory construct validity, internal consistency, and reliability The shortened version has a better response structure and is more readily feasible.